The Impact of Ability and Work Experience on Employee Performance at PT. Petrokopindo Cipta Selaras - Zalzabilla Putri Hartanti; Kustini Kustini (International Journal of Asian Business and Management, 2023)
The purpose of this study is to determine the effect of ability and work experience on employee performance at PT Petrokopindo Cipta Selaras. The population in this study were all employees of PT Petrokopindo Cipta Selaras, a total of 197 employees. By using the slovin formula, the number of samples used in this study were 66 respondents from 5 divisions. Sampling using probability sampling technique, using proportional random sampling method. The research method used in this study was interviews and questionnaires. Data analysis used Partial Least Square (PLS) with an ordinal measurement scale via a Likert scale. The research results show that; (ability has an impact on employee performance (2) experience has no impact on employee performance because the company's targets have been met but not followed by the results of good performance appraisal indicators